Peningkatan Nilai Tambah Komoditas Labu Madu (Butternut Squash) Menjadi MILADU (Mie Labu Madu) di Desa Pudak - Ronaldo Aidil Putra; Heriberta; Nurida Isnaeni; Ridhwan; Muhammad Roihan (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2023)
The Village Innovation Program (PRO IDE) aims to increase the added value of honey pumpkin (butternut squash) commodities produced by community agriculture into processed food products in the form of honey pumpkin noodles. The stages of implementing this activity are: (1) socialization of the activity to the honey pumpkin partner community in Pudak village, (2) selection of raw materials, preparation of tools and other infrastructure, (3) practice of processing honey pumpkin noodles, (4) assistance in the licensing process halal products and certification, (5) digital marketing training, and (6) monitoring and evaluating activities. The results of this service activity provide an alternative solution for honey pumpkin partner communities in marketing their agricultural commodity products in the form of honey pumpkin noodles which have been standardized with legal licensing so that it will be easy to market these processed food products. The conclusion from this service is that the honey pumpkin noodle product is an alternative to increase added value for honey pumpkin to achieve economic added value. With the results of the activities, the PIB UKM Pro Ide Team assisted and developed the rejected honey pumpkins in Pudak Village by processing the pumpkins into a processed product, namely instant noodles. It is hoped that this assistance and development in processing honey pumpkin into instant noodle products can overcome the problem in Pudak Village, namely that the rejected honey pumpkin becomes a product that has sales value and can be remarketed in the form of noodles, which will hopefully add to the economy of the community in Pudak Village. can improve the welfare of the Pudak village community.